The Impact of Heat Styling Tools on Hair Health Through the Project-Based Learning (PjBL) Model in the Hair Straightening Course - Israwati Hamsar (Information Technology Education Journal, 2025)
This study aims to analyze the impact of using heat styling tools such as flat irons and hair dryers on hair health through the implementation of the Project-Based Learning (PjBL) model in the Hair Straightening course. The method used is descriptive quantitative, with data collected through questionnaires distributed to eight student clients participating in the learning project. Data analysis was conducted using Pearson correlation test, linear regression, and Paired Sample T-Test. The results showed a positive and significant relationship between the frequency of heat tool usage and the level of hair damage (r = 0.785; p < 0.05). In addition, heat styling tools contributed 61.6% to changes in hair condition (R² = 0.616), and there was a significant difference between hair conditions before and after using the tools (t = 5.321; p < 0.05). These findings confirm that excessive use of heat styling tools has a negative impact on hair health. Therefore, education through project-based learning practices is needed to encourage more wise and safe use of styling tools.